1995
DOI: 10.1016/0035-9203(95)90531-6
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological survey of rickettsial infections among blood donors in central Tunisia

Abstract: In this report we attempt to evaluate the prevalence of antibodies against Rickettsia conorii, R. typhi, Coxiella burnettii, and Ehrlichia chaffeensis in central Tunisia. Five hundred sera from blood donors, collected between March and June 1993, were tested for these 4 antibodies using an indirect immunofluorescence antibody assay (IFA). Nine percent of the sera had antibodies against R. conorii (IgG > 1:32) by IFA, and 8% by Western blotting; with IFA, 3.6% had antibodies to R. typhi, 26% to C. burnetii (> 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 8 publications
2
29
0
Order By: Relevance
“…6 From 1984 to 1992, using a sensitive and specific test for the diagnosis of rickettsial infections, typhus was diagnosed in our hospitals 7 and relatively high seroprevalence was detected among febrile patients and blood donors in the region (central Tunisia). 8,9 In this study the epidemiological and clinical characteristics of murine typhus are reported with the aim of warning physicians of the persistence or re-emergence of the disease in Tunisia.…”
Section: Introductionmentioning
confidence: 99%
“…6 From 1984 to 1992, using a sensitive and specific test for the diagnosis of rickettsial infections, typhus was diagnosed in our hospitals 7 and relatively high seroprevalence was detected among febrile patients and blood donors in the region (central Tunisia). 8,9 In this study the epidemiological and clinical characteristics of murine typhus are reported with the aim of warning physicians of the persistence or re-emergence of the disease in Tunisia.…”
Section: Introductionmentioning
confidence: 99%
“…Mediterranean spotted fever (MSF) is caused by Rickettsia conorii and is a disease described for the first time in Tunisia (2) and the most frequently observed spotted fever infection recorded in public hospitals. However, many clinical, serological, and molecular studies have demonstrated the presence of R. conorii, Rickettsia felis, and Rickettsia typhi in patients (3,4,5,6). A high seroprevalence was also detected among Tunisian blood donors: 8% tested by Western blotting showed the characteristic profile of R. conorii (3).…”
mentioning
confidence: 99%
“…However, many clinical, serological, and molecular studies have demonstrated the presence of R. conorii, Rickettsia felis, and Rickettsia typhi in patients (3,4,5,6). A high seroprevalence was also detected among Tunisian blood donors: 8% tested by Western blotting showed the characteristic profile of R. conorii (3). Despite the longstanding presence of the rickettsiosis and its medical importance in Tunisia, the arthropod vectors have been poorly investigated.…”
mentioning
confidence: 99%
“…20 Ge ne rally, stu di es in dica te that the Q fe ver pre va len ce is hig her in ru ral zo nes com pa red to ur ban zo nes, 14,20,22,[27][28][29] ho we ver the re are so me stu di es re por ting no sig ni fi cant corre la ti on bet we en se ro po si ti vity and the pla ce of resi den ce. 19,23 In our study, the samp les we re ob ta i ned mostly from ru ral zo nes. Ho we ver, our po pu la ti on only inc lu ded the high-risk oc cu pa tions; in this res pect such a com pa ri son wo uld be unap prop ri a te.…”
Section: Discussionmentioning
confidence: 99%
“…Si mi lar reports ha ve be en pub lis hed re gar ding the pre va len ce of C. bur ne ti i in fec ti on be ing mo re fre qu ent in men in Spa in, Fran ce, Aus tra li a and Tu ni si a. [21][22][23] The pre va len ce of C. bur ne ti i in fec ti on se ems to vary in dif fe rent ge og rap hic are as and po pu la tions. The pre va len ce ra tes may al so vary ac cor ding to the tech ni qu es used for the de tec ti on of an ti bodi es and in ter pre ta ti on of the po si ti ve re sults.…”
Section: Discussionmentioning
confidence: 99%